The rise and fall of FidoNet: the geographic growth and decline of an ICT community - Rees, G (2014)
This thesis studies the time evolution of a computer mediated community called FidoNet. The introduction explains what FidoNet is, briefly details its history and sociological significance and sets out research goals for the thesis as a whole. The second chapter—covering background and relevant literature—relates FidoNet to other social phenomena and reviews relevant sections of work on dynamic approaches to social systems. It also describes how FidoNet Nodelists were combined with geographic data on US telephone lines and 1990 Census data so that the geographic growth and decline of FidoNet could be mapped and analysed. The third through fifth chapters are substantive starting with an empirical analysis on the spatial growth of FidoNet in the United States, covering a variety of different ways in which distance could have mediated the contagiousness of FidoNet as a system. The fourth considers decline as a similarly contagious process, demonstrating that FidoNet’s most obvious competitor—the internet—may in fact have discouraged its decline while the short-term influence of leaving events on current sysops fits the data far better as an explanation. The other explanatory variable of this section—long-term social influence—exhibits an unexpected sign, suggesting that perhaps there were incentives to maintain FidoNet that were most prevalent in the long-term. The fifth chapter attempts to tease out which different mechanisms may have been at work during decline, using an Agent-Based Modelling (ABM) approach and specifically considering individual rather than aggregated behaviour. The 6th and final chapter summarises the findings.